PROJECT PLANNING PEMBANGUNAN JALAN LINTAS SELATAN PANTAI SINE – BATAS KABUPATEN BLITAR I - Mohammad Haikal Asshidiqie; Indah Ria Riskiyah; Fadjar Purnomo (Jurusan Teknik Sipil Politeknik Negeri Malang, 2024)
The Project Planning of Development of Trans South Road Sine Beach – Blitar District Border 1, located in Tulungagung District, with the total length is 6.55 km. The challenging and remote terrain, logistical activities, as well as adverse weather conditions, have caused delays in the project, necessitating an accurate and efficient project planning. This project can be realized by considering cost, time, and good quality. The objectives of this project planning are including appropriate organizational structure planning, site layout, execution strategies and methods, quality planning, occupational health and safety planning, implementation budget planning, and project work scheduling. The required data includes project drawings, work plans and specifications, and the list of labor unit prices in Tulungagung District 2023. Project cost estimation is performed using Microsoft Excel 2019, and scheduling and the use of the S-curve are achieved through the Gantt Chart method using Microsoft Project 2016. This Project Planning results in a pure project organizational structure, 2 alternative site layout options, execution strategy divided into 4 zones, quality control carried out through work implementation inspections and material testing, and occupational health and safety control applied in the project involves identifying potential hazards in the work environment (HIRARC), with a duration of 336 calendar days and a total implementation cost is Rp283,573,377,000.00.